Monopoly Agenda Control and Asymmetric Information - Banks, Jeffrey S. (Quarterly Journal of Economics, 1990)
This paper extends the Romer-Rosenthal [1978, 1979] model of monopoly agenda control to an environment where only the agenda setter knows with certainty the outcome associated with a failed proposal. The presence of this asymmetric information implies that any "take-it-or-leave-it" proposal may provide information crucial to the decision calculus of the voters, a fact which an optimal proposal strategy will incorporate. The equilibrium behavior of the agenda setter and voters is characterized and contrasted with that in the complete information environment, and a number of empirical predictions concerning the nature of elections with monopoly controlled agendas are derived.